Split luciferase-based assay to detect botulinum neurotoxins using hiPSC-derived motor neurons - Laurent Cotter; Feifan Yu; Sylvain Roqueviere; Juliette Duchesne de Lamotte; Johannes Krupp; Min Dong; Camille Nicoleau (Communications Biology, 2023)
A cell-based assay for detecting SNAP25-cleaving Botulinum neurotoxins (BoNTs) is developed by combining hiPSC-derived motor neurons and a luminescent detection system based on split NanoLuc luciferase.